Association of Balance deficits and Risk of fall in Patient with Diabetes Mellitus - Ahmed, Zalan; Yasmeen, Hina; Muskan, Rahiya; Orakzai, Sheeba; Waseem, Ansa; Khan, Hafiz Yaseen (Indus Journal of Bioscience Research, 2025)
Background: Diabetes Mellitus (DM) is a long-term metabolic disease majorly typified by hyperglycemia. The purpose of this study was to explore the association between balance deficits and the risk of falls in diabetic patients. Methodology: A descriptive cross-sectional study was carried out to analyze the relationship between balance deficits and risk of falling among 101 diabetic patients aged between 18 and 40 years. The research was conducted between November 2024 and April 2025 at Lady Reading Hospital, Peshawar. Balance functions were assessed with the use of the Berg Balance Scale (BBS), and falling risk was determined with the Timed Up and Go test. Informed consent was taken from all the participants, and ethical clearance was provided by the Departmental Research Committee of the City University of Science and Information Technology. Results: The findings indicated that 30.7% of the participants had poor balance, 24.8% had fair balance, and 44.6% had good balance. On evaluating fall risk, 45.5% had normal mobility, 18.8% were in the borderline group, and 35.6% had abnormal mobility. There was a statistically significant correlation between balance deficits and fall risk (p = 0.000) with increased abnormal mobility in poor balancers. These findings emphasize the importance of early detection and focused rehabilitation programs in young diabetic individuals. Conclusion: Even with poor balance considered, diabetes remains a major risk factor for falls, influenced by higher medication use and reduced cognitive function. Risk of falling increases as balance worsens. The study found that about half the participants mostly men had poor balance and elevated fall risk, with a strong link between balance deficits and fall risk.